A new larval species of Erythraeus (Zaracarus) (Acari: Erythraeidae) from southeastern Iran - Abdolazim Mortazavi; Hamidreza Hajiqanbar; Alireza Saboori (Persian Journal of Acarology)
The mite species Erythraeus (Zaracarus) coleopterus sp. nov. (Acari: Parasitengona: Erythraeidae) associated with a scarabaeid beetle is described from Iran. This is the first record of association between mites of the genus Erythraeus and beetles.